2016
DOI: 10.1370/afm.1888
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Exchange Health Information via Mobile Devices: Findings From a Population-Based Survey

Abstract: PURPOSEThe rapid proliferation of mobile devices offers unprecedented opportunities for patients and health care professionals to exchange health information electronically, but little is known about patients' willingness to exchange various types of health information using these devices. We examined willingness to exchange different types of health information via mobile devices, and assessed whether sociodemographic characteristics and trust in clinicians were associated with willingness in a nationally rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 22 publications
7
52
2
4
Order By: Relevance
“…These types of problems need to be addressed if the aim is to share data across sectors. Previous research relating to the use of personal electronic health records has demonstrated less public and professional appetite than anticipated [22,44]. …”
Section: Discussionmentioning
confidence: 99%
“…These types of problems need to be addressed if the aim is to share data across sectors. Previous research relating to the use of personal electronic health records has demonstrated less public and professional appetite than anticipated [22,44]. …”
Section: Discussionmentioning
confidence: 99%
“…Personalised interventions based on shared decision-making with patients are more likely to have positive outcomes, as involving patients in deciding the time and method for receiving interventions from healthcare providers minimises annoyance from constant notification of health messages [34]. In addition, studies have found that receptivity towards mobile phone text messages as a healthcare intervention reduces with increasing age, as well as with lower education and income levels [35]. Therefore, clinicians and policymakers need to be cognizant of this and provide additional strategies for certain patient groups.…”
Section: Medicines Management In Daily Lifementioning
confidence: 99%
“…First, it is unclear which types of patients with cancer would benefit most from being monitored by using IoT technologies, which types of data will be necessary to accurately capture the quality of care and improve patient outcomes, and how frequently data should be sampled (continuously v intermittently). Second, while a recent national survey showed that patients are quite willing to exchange information about vital signs and symptoms over a mobile phone or tablet, 12 little is known about whether patients would be willing to be continuously monitored with IoT technologies that might be perceived as being more obtrusive. Third, providers who are already inundated with data are wary about the impact of additional data on their workflows and workload.…”
mentioning
confidence: 99%